Characterization of staphylococcal small colony variants and their pathogenic role in biomaterial-related infections with special reference to staphylococcus epidermidis - Matar, Suzan (2004)
There are many surgical implanted devices in current use and all are prone to biomaterial-related infections (BRI) associated with staphylococcal biofilm formation. BRI are usually associated with S. epidermidis or S. Aureus and are characterized by treatment failure and chronicity resulting in reoperation, removal of the implant, and loss of function or death. Staphylococcal small colony variants (SCVs) may be generated by exposure to sublethal concentrations of antibiotics or nutrient limitation which may occur in biofilms. Although the characteristics of S. aureus SCVs have been well studied, little information on SCVs of S. epidermidis and their potential role in BRI is currently available. This study was designed to investigate the biochemical and phenotypic characteristics of S. epidermidis SCVs to further identify characteristics which may contribute to their ability to cause these increasingly important infections.